PENINGKATAN KEPUASAN KERJA PELAUT MELALUI KEBIJAKAN PENGUPAHAN DAN KESEMPATAN PENGEMBANGAN KARIR - HARTOYO, POPO (UNIMAR AMNI Semarang, 2025)
This research examines wage policies and career development opportunities which are thought to influence job satisfaction at the Shipping Company PT. X. The reason for this research was to find out whether salary is absolutely necessary in an organization/company, assuming this can motivate sailors at work. The next reason is whether there are career development opportunities that are also a consideration for seafarers to join the PT Shipping Company. X. These two factors will then be studied to determine their impact on job satisfaction at the Shipping Company PT. X. Questionnaires were given to 358 selected respondents and analyzed using multiple linear regression tests. The results of the research concluded that wage policies and career development opportunities did not have a significant effect on job satisfaction at shipping company X.Keywords: Wage Policy, Career Development Opportunities, Job Satisfaction